2011
DOI: 10.1371/journal.pone.0019216
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Galectin-3 Disturbs Mesenteric Lymph Node Homeostasis and B Cell Niches in the Course of Schistosoma mansoni Infection

Abstract: Galectin-3 is a β-galactoside-binding protein that has been shown to regulate pathophysiological processes, including cellular activation, differentiation and apoptosis. Recently, we showed that galectin-3 acts as a potent inhibitor of B cell differentiation into plasma cells. Here, we have investigated whether galectin-3 interferes with the lymphoid organization of B cell compartments in mesenteric lymph nodes (MLNs) during chronic schistosomiasis, using WT and galectin-3-/- mice. Schistosoma mansoni synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
(49 reference statements)
1
23
0
Order By: Relevance
“…[22][23][24] Moreover, gal-3 inhibits B-cell differentiation into plasma cells in distinct lymphoid tissues, [23][24][25] plays anti-apoptotic functions on proliferative B-cell neoplasms 26 and maintains B-cell anergy. 27 The advent of gal-3 deficient mice (gal-3 À/À mice) allowed more detailed studies on immunomodulatory mechanisms of gal-3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24] Moreover, gal-3 inhibits B-cell differentiation into plasma cells in distinct lymphoid tissues, [23][24][25] plays anti-apoptotic functions on proliferative B-cell neoplasms 26 and maintains B-cell anergy. 27 The advent of gal-3 deficient mice (gal-3 À/À mice) allowed more detailed studies on immunomodulatory mechanisms of gal-3.…”
Section: Introductionmentioning
confidence: 99%
“…24,31,32 Gal-3 À/À mice have an intense plasmacytogenesis and hypergammaglobulinemia as well as follicular B cells highly susceptible to apoptotic stimuli. [22][23][24] In addition, autoantibody transgenic mice lacking gal-3 (and also gal-1) have spontaneous anti-laminin-secreting plasma cell differentiation in the spleen followed by B-cell depletion and anergy. 27 These data suggest that gal-3 plays a central role in maintaining B-cell tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, we demonstrated that S. mansoni-infected Lgals3 −/− mice have hyperglobulinemia and intense plasmacytogenesis in the bone marrow, mesenteric lymph nodes and spleen (Brand et al 2012;Oliveira et al 2007Oliveira et al , 2011. Here, we propose a new regulatory role for galectin-3 in IgA + plasma cell differentiation in the peritoneal cavity during chronic schistosomiasis inflammation and during IL-5 and TGF-β1 treatment in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 60%
“…Immediately after extirpation, the omentum was fixed for 24 h in 10 % buffered formalin, dehydrated and embedded in paraffin. Tissue sections (5 μm thick) were stained with hematoxilin and eosin or processed for further immunohistochemistry analysis (Oliveira et al 2011). The tissue was analyzed by a light microscope (Zeiss-Axioplan, Jena, Germany) and images were acquired by bright field microscopy via a camera (Evolution MP 5.0 RTV-Color-Media Cybernetics, Canada).…”
Section: Histological Analysis Of Mesentery and Omentummentioning
confidence: 99%
See 1 more Smart Citation